A Fluorescent Probe for Hydrazine Based on 4-hydroxycoumarin with High Selectivity and Sensitivity - Fang, Fang; Han, Wendi; Ke, Fang; Liu, Shun; Li, Lipeng; Wu, Mei (Current Analytical Chemistry, 2024)
Background: Hydrazine may induce gene abnormalities, cancer, and severe damage to the liver, lungs, kidneys, and central nervous system. Therefore, the development of reliable analytical techniques with high selectivity and sensitivity to detect hydrazine is required for the protection of human health and safety. Objectives: Traditional methods for detecting N2H4 are frequently time-consuming, less accurate, and unsuitable for the analysis of living systems. Numerous fluorescent probes for hydrazine have been produced and gained some valuable results recently. The creation of a simple fluorescent probe for hydrazine detection is the goal of this project. Method: In this study, 300 μL of probe 3-methyl-2-oxo-2H-chromen-7-yl propionate (MOCP) was mixed with an equivalent amount of the solution of each analyte to obtain the measurement solution. Following a 10-minute room temperature incubation period, the fluorescence spectra of the resultant solution were recorded. Results: The fluorescence intensity of the probe was noticeably enhanced when N2H4 was added to the probe, but almost no fluorescence enhancement was observed when other competitive ions were added. Conclusion: A hydrazine fluorescent probe based on 4-hydroxycoumarin fluorophore was developed. The probe MOCP displayed high sensitivity and selectivity for hydrazine, with a color change from colourless to blue for detection by the naked eye. Moreover, it demonstrated a low detection limit of 20 nM and a fast reaction time of 30 s.
Keywords: probes